The historiography of Alexander the Great - Nawotka, Krzysztof; Rollinger, Robert; Wiesehöfer, Josef; Wojciechowska, Agnieszka (Classica et orientalia, 2019)
Cover -- Title Pages -- Imprint -- Contents -- Krzysztof Nawotka, Josef Wiesehöfer and Agnieszka Wojciechowska: Historiography of Alexander the Great: An Introduction -- Pierre Briant: Alexandre à Troie: images, mythe et realia -- Kenneth R. Moore: Of Philosophers and Kings: Concerning Philip II of Macedon's Alleged "Debt" to Plato -- Nicolas Sekunda: Patron the Phocian: a written "mercenary source" -- Reinhold Bichler: On the Traces of Onesicritus. Some Historiographical Aspects of Alexander's Indian Campaign -- Adam Łukaszewicz: Alexander and the palace of Memnon -- Ivan Ladynin: Cleomenes of Naucratis in Pseudo-Aristotle's Oeconomica and the topoi of the Ancient Egyptian Propaganda -- Robin Lane Fox: P.OXY. 4808 and Historians -- Gościwit Malinowski: Agatharchides of Cnidus and the idea of a Peripatetic view of Alexander -- Federicomaria Muccioli: In search of the many images of Alexander at Chaeronea. Historical and literary traditions in Plutarch's „Corpus" -- Sabine Müller: The Miracles of Water and Oil in the Historiography on Alexander -- Giuseppe Squillace: The subtle and red line between reality and fiction: Alexander and his 'Propaganda Machine' -- Krzysztof Nawotka : I Maccabees and the Alexander Romance -- Ory Amitay: Alexander and Caligula in the Jerusalem Temple: A Case of Conflated Traditions -- Corinne Jouanno: The Alexander historians in Byzantium -- Bibliography -- Indices.